Розробка інформаційно-аналітичної системи для навігації в метрополітені - Нечаєва, Я. Є. (ХНУРЕ, 2024)
The report discusses the development of an information-analytical system for subway navigation using a width-first search algorithm to find the shortest path from station to station. This system aims to simplify orientation in the subways of large cities of Ukraine and improve the experience of using the subway.
Keywords: інформаційно-аналітична система; навігація метрополітеном; система навігації